FORMATION OF ACTIVE PROFESSIONAL POSITION OF FUTURE TEACHERS BY MEANS OF USING INTERACTIVE METHODS OF TEACHING IN THE PROCESS OF STUDY TEACHING - Shcherbyna, S.M.; Shcherbyna, I.Yu. (Pedagogy of Higher and Secondary Education, 2010)
This article is devoted to forming of active professional position of future teachers by means of using interactive methods of learning during pedagogical training.